Psychological Anxiety of COVID-19 Pandemic and its Effect on Academic Performance of University Students - Ashshawareb, Iyad J.; Alnasraween, Mo’en S.; ALi, Darine Abu; Mustafa, Nadia A.; Ashshawareb, Yanal Iyad (Journal of Ecohumanism, 2024)
The problem and the aim of the study. The COVID-19 pandemic has caused a worldwide emergency, with consequences for more than just physical health, including mental health and educational outcomes. University students are particularly vulnerable since they are dealing with a number of challenges at once, such as the health effects of the pandemic both directly and indirectly, the sudden shift to online schooling, and doubts about their future employment opportunities. Critical to understanding the far-reaching effects of the pandemic on student lives, learning processes, and mental health is research into COVID-19-related psychological anxiety and its impact on academic performance in higher education. This research subject seeks to investigate the extent to which college students are anxious about the COVID-19 pandemic and how this unusual stressor affects their participation in class, grades, and general satisfaction with their education. By looking at it from this perspective, we may identify the many ways in which the epidemic has affected the future generation of researchers and professionals, and then develop strategies to help them cope with the difficulties they will face. Research methods. The study employed a correlational descriptive approach to investigate the psychological distress caused by the COVID-19 epidemic and its influence on the academic performance of university students in Jordan. The sample consisted of 300 undergraduates (male and female) from the College of Educational and Psychological Sciences at Amman Arab University in the 2021–2022 school year, with the entire student body serving as the population. The survey tool was distributed online via social media, leading to 379 respondents, and a chance sample was used because it was feasible to reach a large number of participants—especially during the pandemic. Results. The study results show a detailed range of stress and worry, with average scores varying from 2.8 to 4.1 among 25 items. Major concerns involve social isolation, indicated by an average score of 4.1 for feeling alienated because of social distancing measures, and academic disruptions, with an average score of 4.0 for experiencing a lack of control over academic life owing to the pandemic. There is a significant gender gap between the reported levels of anxiety and its effect on academic performance; 40% of female students and 30% of male students express high levels of anxiety, and the average academic impact score for female students is 3.0 while the average score for male students is 2.5. The data also shows that anxiety levels and the detrimental effect they have on academic performance are getting worse over the years, with fourth-year students having the worst levels of anxiety (45%) and the greatest academic impact score (3.5). The findings highlight the importance of providing students with personalized support to help them cope with the psychological effects of the pandemic. Scientific novelty: Novelty resides in the study's exhaustive examination of COVID-19's psychological effects on Jordanian university students, with a particular emphasis on anxiety levels and how they relate to academic achievement. By looking at the effects of the pandemic across genders and academic years, it shows how anxiety levels rise over time and how there are clear differences between the sexes. The study offers important insights into the many ways in which the pandemic affected students' academic performance and mental health by using a large sample size, a correlational descriptive approach, and social media to reach a wide audience during the epidemic.